Pengaruh Kualitas Daya Tarik Wisata Terhadap Kepuasan Wisatawan Di Pantai Lovina, Kabupaten Buleleng: Pengaruh Kualitas Daya Tarik Wisata Terhadap Kepuasan Wisatawan Di Pantai Lovina, Kabupaten Buleleng - Puspita, Ni Made Nandila; Negarayana, Ida Bagus Putra; Aridayanti, Dewa Ayu Nyoman (Journal of Applied Science in Tourism Destination, 2024)
The quality of tourist attractions has a significant influence on tourist satisfaction, because tourist attractions that offer unique experiences, beautiful views and interesting activities will increase tourist satisfaction. The aim of this research is to determine the influence of the quality of tourist attractions on the satisfaction of Indonesian tourists at Lovina beach. The number of samples in this study was 110 respondents using the formula of Hair et al. Data collection in this research was carried out by distributing questionnaires to all Indonesian tourists who were visiting Lovina beach. The data analysis technique used in this research is a simple linear regression analysis technique, t test and coefficient of determination with data analysis tools using the help of the SPSS for Windows version 26 program. The results in this study show that the quality of tourist attractions has a significant effect on tourist satisfaction. at Lovina Beach with a significant value of 0.000 < 0.050. The magnitude of the influence of the quality of tourist attractions on the satisfaction of Indonesian tourists at Lovina Beach is 0.685, which means 68.5% of the satisfaction of Indonesian tourists is influenced by the variable quality of tourist attractions.